Me and the Robbersons - Kolu, Siri 1972- (Little Tiger, 2021)
Maisie is convinced her summer holiday is going to be as boring as ever - until a bungled raid on her family's car sees her snatched by the Robbersons, a bunch of bandits with an insatiable appetite for sweets! Soon Maisie realises that life on the open road with the Robbersons is the adventure she's always longed for. They've even started to see her as one of the gang! So when she discovers that the police and her parents are hot on their trail, Maisie decides she isn't quite ready to be rescued ...
Originally published in Finnish as Me Rosvolat by Otava, 2010
Keywords: Abenteuer; Räuber; Familie; Entführung; Reise; Tochter; Finnland; Vacations / Juvenile fiction; Kidnapping / Juvenile fiction; Brigands and robbers / Juvenile fiction; Candy / Juvenile fiction; Bandits et brigands / Romans, nouvelles, etc. pour la jeunesse; Bonbons / Romans, nouvelles, etc. pour la jeunesse; Histoires pour enfants; Brigands and robbers; Action and adventure fiction; Kinderbuch